2016
DOI: 10.1200/jco.2016.34.26_suppl.4
|View full text |Cite
|
Sign up to set email alerts
|

Cancer versus non-cancer caregivers: An analysis of communication needs from the 2015 Caregivers in the U.S. study.

Abstract: 4 Background: Informal caregiving for cancer patients can be both demanding and burdensome – physically, emotionally, and financially – for many caregivers. Cancer caregivers play a large role in advocating for and administering care for their recipients. The current study aimed to explore if cancer caregivers differ from non-cancer caregivers with regard to communicating with healthcare providers, and need for information about end-of-life care. Methods: Data were used from the 2015 Caregiving in the U.S. (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…However, caregivers who report feeling more prepared for the caregiving experience report lower levels of personal strain during cancer care [ 9 , 11 ]. Cancer caregivers experience greater burden than non-cancer caregivers in the U.S., and provide more hours of caregiving per week, and cancer caregivers need significantly more help making end of life decisions than do non-cancer caregivers [ 13 ].…”
Section: The Family Caregiver and Palliative Care Growthmentioning
confidence: 99%
“…However, caregivers who report feeling more prepared for the caregiving experience report lower levels of personal strain during cancer care [ 9 , 11 ]. Cancer caregivers experience greater burden than non-cancer caregivers in the U.S., and provide more hours of caregiving per week, and cancer caregivers need significantly more help making end of life decisions than do non-cancer caregivers [ 13 ].…”
Section: The Family Caregiver and Palliative Care Growthmentioning
confidence: 99%
“…Increasing numbers of cancer patients require more caregivers who are broadly known as a friend or relative providing unpaid care for a person with a chronic or disabling condition . Compared with the caregivers of noncancer patients, caregivers of patients with cancer spend more time on caregiving (32.9 vs 23.9 hours per week) . A study reported that cancer patient caregivers spend approximately 8.3 hours per day caring for cancer patients with distant metastasis .…”
Section: Introductionmentioning
confidence: 99%
“…Although evidence indicates that family members caring for cancer patients have a higher burden, 35 there is less literature on the family support needs for non-cancer conditions. 7 In this study, half of the participants were in the latter group.…”
Section: Discussionmentioning
confidence: 99%
“…Logistic regression models were performed separately for carers of cancer patients and those of non-cancer patients, as evidence indicates that their support needs vary. 35 Statistical significance was set at α = 0.05.…”
Section: Methodsmentioning
confidence: 99%